2020
DOI: 10.1098/rspb.2019.2794
|View full text |Cite
|
Sign up to set email alerts
|

Social norms and cultural diversity in the development of third-party punishment

Abstract: Human cooperation is probably supported by our tendency to punish selfishness in others. Social norms play an important role in motivating third-party punishment (TPP), and also in explaining societal differences in prosocial behaviour. However, there has been little work directly linking social norms to the development of TPP across societies. In this study, we explored the impact of normative information on the development of TPP in 603 children aged 4–14, across six diverse societies. Children began to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 38 publications
(64 reference statements)
3
57
0
3
Order By: Relevance
“…To examine whether these patterns held true within populations, we next conducted an assessment of risk and time preferences between Shuar children in more and less-integrated communities, and found the same pattern of results: Shuar children in peri-urban communities were more risk-tolerant and future-oriented than their counterparts in the remote, rainforest communities (Amir, Jordan, et al, 2019) . This form of work, in which initial waves of data generate novel predictions to be tested in subsequent waves -also demonstrated nicely in (House et al, 2013(House et al, , 2019(House et al, , 2020 -represent ways in which multiple key insights can be integrated into a unified research question.…”
Section: Promising Directions In Cross-cultural Developmental Sciencementioning
confidence: 81%
See 2 more Smart Citations
“…To examine whether these patterns held true within populations, we next conducted an assessment of risk and time preferences between Shuar children in more and less-integrated communities, and found the same pattern of results: Shuar children in peri-urban communities were more risk-tolerant and future-oriented than their counterparts in the remote, rainforest communities (Amir, Jordan, et al, 2019) . This form of work, in which initial waves of data generate novel predictions to be tested in subsequent waves -also demonstrated nicely in (House et al, 2013(House et al, , 2019(House et al, , 2020 -represent ways in which multiple key insights can be integrated into a unified research question.…”
Section: Promising Directions In Cross-cultural Developmental Sciencementioning
confidence: 81%
“…While the House et al (2013) study provides a compelling example of why a multi-site approach is useful and how it can inform theories of cross-cultural development, additional work by members of the same research team demonstrates how experimental approaches can build upon and enrich these findings. Recently, the team built upon their previous work by using a similar paradigm to explore how cross-societal variation in norms and an emerging norm psychology interact to influence children's social behaviors, such as generosity (House et al, 2019) and third-party punishment (House et al, 2020) . Critically, these studies involved an experimental manipulation: the authors showed children videos of an adult demonstrating a novel normmodeling, for instance, either selfish or generous behavior (House et al, 2019) -to explore how sensitivity to normative behavior shapes children's decision-making in these settings.…”
Section: Breadth: Standardized Approaches and Multi-culture Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesqui. | Juiz de Fora | 14(4) | 196-220 | 2020DOI: 10.34019/1982-1247.2020 Naegeli supostamente reforçados positivamente pela possibilidade de obtenção de retorno futuro (Ferreira, 2018).…”
Section: Teste De Preferênciaunclassified
“…Pesqui. | Juiz de Fora | 14(4) | 196-220 | 2020DOI: 10.34019/1982-1247.2020 psicóticos quando havia uma demora longa entre o comportamento e o reforço (Ayllon & Azrin, 1965). Nesse caso, a instituição de saúde esperava que os pacientes participassem das rotinas de trabalho, como lavar louça e servir refeições.…”
unclassified